Frictional, thermal, and total entropy generation of two-phase nanofluid turbulent flow in a circular heatsink: A numerical study. (May 2023) - Mustafa, Jawed; Abdullah, M.M.; Ahmad, Mohammad Zaki; Jamil, Basharat; Sharifpur, Mohsen
Abstract: This article presents a numerical study on entropy generation (ETG), including thermal, frictional, and total ETG of alumina/water nanofluid (NFD) flow in an aluminum heatsink (HSK). The HSK with reciprocating channels is designed to cool seven LEDs. The NFD flow is in a turbulent regime and is analyzed using a two-phase model. The HSK is circular and includes two inlets on two different sides and four outlets on the other two sides. COMSOL software is employed to simulate the HSK. The amounts of pressure and temperature in the HSK channels are estimated. The results demonstrate that frictional ETG changes from 0.17 W/s to 5.37 W/s in the range of studied variables. Frictional ETG is larger than thermal ETG, and as a result, the effect of frictional ETG on total ETG is greater. The maximum and minimum values of total ETG are 5.37 W/s and 0.17 W/s which occur at the maximum and minimum NFD velocities, respectively. The maximum value of thermal ETG corresponds to the smallest dimensions of heat sources and the minimum NFD velocity. The minimum amount of thermal ETG is related to the largest dimensions of heat sources and the maximum NFD velocity.